Fiber-Optic Communication Systems (5th Edition) - Agrawal, G. P. (Govind P.) (Wiley Series in Microwave and Optical Engineering, 2021)
In the newly revised Fifth Edition of this book, accomplished researcher and author, author, delivers brand-new updates and developments in the science of fiber optics communications. The book contains substantial additions covering the topics of coherence detection, space division multiplexing, and more advanced subjects. You'll learn about topics like fiber's losses, dispersion, and nonlinearities, as well as coherent lightwave systems. The latter subject has undergone major changes due to the extensive development of digital coherent systems over the last decade. Space-division multiplexing is covered as well, including multimode and multicore fibers developed in just the last ten years. Finally, the book concludes with a chapter on brand-new developments in the field that are still at the development stage and likely to become highly relevant for practitioners and researchers in the coming years.